Growth response, yield, and quality of bread wheat, Triticum aestivum L. For spraying with ascorbic acid and tocopherol (Texas Journal of Agriculture and Biological Sciences, 2023)
A field experiment was carried out at the Agricultural Research and Experiment Station affiliated with the College of Agriculture - University of Basra during the winter of 2021-2022. To study the response of growth and yield of bread wheat to spraying with ascorbic acid and tocopherol.